ANALISIS BENTUK PRODUK KERAMIK STUDIO MANDIRI DENGAN TEMA TRADISI LOKAL INDONESIA MELALUI PENDEKATAN ‘ATUMICS’ - Ardini, Sasanti Puri; Winata, Gita (Panggung, 2023)
Indonesia, known for its rich cultural diversity and traditional practices, offers a wide range of ceramicproducts that have a strong basis in tradition. These creations appear from the artistic endeavors ofindividual artists, independent studios, and craft-based industries. The scope of diversity extends beyondthe topic of the field of tradition, which includes a combination of technical abilities and materials usedfor the creation of a piece, thus implementing a transformation of a local tradition into an innovativeand creative product. This article present an exhibition and analysis of independent studio and craftbased industries ceramics products that explore the theme of local Indonesian traditions through theapplication of the The ATUMICS method is a way of Transformation Tradition that was introduced byAdhi Nugraha. The study using the ATUMICS framework, which refers Artifact (A), Technique (T),Utility (U), Material (M), Icon (I), Concepts (C) and Shape (S). These models were utilized to definethe components that were found in ceramics products originating from three different ceramic studioor craft-based industries in Indonesia. The research results provide insight into which elements can beapplied and combined through the ATUMICS method to enhance local traditions in ceramics.Keywords: ceramic, craft, product, tradition, atumics